Antibacterial, bacteriolytic, antibiofilm, and synergistic effects of Curcuma species ethanol extracts with antibiotic against multidrug resistant Pseudomonas aeruginosa - Yuandani Yuandani; Abdi Wira Septama; Dinda Sari Utami; Sony Eka Nugraha; Sufitni Sufitni; Nur Aini Khairunnisa; Halimah Raina Nasution; Ramaza Rizka (Shahrekord University of Medical Sciences, 2024)
Introduction: Curcuma species have shown antibacterial activity against Pseudomonas aeruginosa. The current study was conducted to analyze the antibacterial activity of ethanol extracts of Curcuma species rhizomes, including Curcuma domestica, C. xanthorrhiza, C. mangga, C. zedoaria, and C. aeruginosa against multidrug-resistant Pseudomonas aeruginosa (MDR P. aeruginosa). Furthermore, the mechanism action of Curcuma species in combination with antibiotic against MDR P. aeruginosa and its chemical component were also investigated. Methods: Determination of minimum inhibitory concentration (MIC) was carried out by the microdilution method. The synergistic effects of the extract and tetracycline were determined by the checkerboard method. The effect of the combination of Curcuma species and tetracycline to prevent bacterial resistance was investigated using inhibition of biofilm formation, permeability of bacterial cell membrane, and EtBr accumulation methods. Gas chromatography-mass spectrometry (GC-MS) analysis was also performed. Results: MIC of C. domestica, C. xanthorrhiza, and C. mangga against MDR P. aeruginosa were 125, 250, and 125 µg/mL, respectively. C. xanthorrhiza ethanol extract (7.8 µg/mL) in combination with tetracycline (1.9 µg/mL) revealed a synergistic activity with Fractional Inhibitory Concentration Index (FICI) value of 0.06. The combination of C. xanthorrhiza ethanol extract and tetracycline showed inhibitory effects on biofilm formation and efflux pump of MDR P. aeruginosa. This combination also had bacteriolytic activity. GC-MS analysis led to the identification of ar-turmerone (11.63%) and xanthorrhizol (11.36%) as the major compounds. Conclusion: Combination of C. xanthorrhiza ethanol extract and tetracycline might be developed as an alternative treatment against MDR P. aeruginosa.